Integrated and Segregated Teaching of Language Skills: An Exploration - Gautam, Pitamber (Journal of NELTA Gandaki, 2019)
This article attempts to explore some existing dimensions of integrated and segregated approaches to teaching language skills along with their psychological and methodological foundations. The body of language is built out of various components of skills and aspects fitted together in a natural harmony. They are substantial elements for teaching and learning endeavour. But, nowadays there are serious arguments about whether to choose segregated or integrated approach for teaching language skills in an ESL/EFL classroom. Although the behavioural psychology and structural linguistics pleaded for segregated approach of teaching through Grammar Translation Method and Audio-lingual Method, the communicative movement supported by cognitive psychology and functional linguistics has a strong adherence to integrated approach in teaching language skills with a sole aim of attaining communicative competence. This article is entirely based on document analysis method, a major component of qualitative research design. The study arrived to conclude that the current communicative movement in foreign language teaching significantly stresses on integrated teaching of language skills. This approach of teaching was proposed in different language teaching methods and models. Among them, Content Based Instruction and Task Based Instruction are the two major methods introduced for integrated language teaching. Now, it has been inferred that integrated approach of language teaching is sure to pursue its hegemony at least for some decades unless a new powerful approach appears to challenge it.